PurrYou furniture a home office smart furniture for monitoring and interacting with cats for cat owners living in limited spaces - Casta, Chantal D.
The COVID-19 pandemic resulted in the increasing trend for cat ownership worldwide, and the Philippines is not an exception to this. Domestic cats are one of the pets that provided companionship and brought numerous benefits to their owners amidst the isolation and restrictions of the pandemic. However, as the world is now transitioning back to normal, there is a change in the daily routine both for the cats and their owners which includes leaving pet cats alone more frequently at home. This poses a challenge for the cat parents as this resulted in a gap in means for them to monitor their cat's overall wellbeing -- regular feeding time, safe environment at home, and adequate resources--and also a convenient way for them to interact and play with their cats even while away from home.